(α, β) – Derivations on Prime Inverse Semirings - Zaghir, Khatam AD.; Majeed , Abdulrahman Hameed (Iraqi Journal of Science, 2021)
Let S be a prime inverse semiring with center Z(S). The aim of this research is to prove some results on the prime inverse semiring with (α, β) – derivation that acts as a homomorphism or as an anti- homomorphism, where α, β are automorphisms on S.